KAJIAN PENDAPATAN ASLI DAERAH KOTA MAKASSAR - Nurmiati Nurmiati; Fina Diana; Murbayani Murbayani (AkMen JURNAL ILMIAH, 2019)
This study aims to obtain a picture of the growth, effectiveness, contribution of each source of PAD to the PAD and prospects for the growth of Makassar City's PAD in the future. This research is a quantitative study using secondary data namely Makassar City PAD data in 2014-2018 by analyzing data such as growth, effectiveness, proportion and trend analysis. The results showed that the Original Revenue of Makassar City for the last 5 years (2014-2018) in terms of growth showed that the realization of PAD experienced an average growth of 14.22% smaller than the average growth in the PAD target of 16.41%. The effectiveness of PAD as measured by the achievement of targets over the past 5 years is quite effective (83.18%). The contribution from each source of PAD shows the highest local tax contributing 77.56%, while the income from the results of the management of the separated Regional Assets is classified as the lowest at only 2.12%. Makassar City's PAD growth prospects in the future shows an increase every year